2008
DOI: 10.1677/jme-08-0039
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen treatment up-regulates female genes but does not suppress all early testicular markers during rainbow trout male-to-female gonadal transdifferentiation

Abstract: In non-mammalian vertebrates, estrogens are key players in ovarian differentiation, but the mechanisms by which they act remain poorly understood. The present study on rainbow trout was designed to investigate whether estrogens trigger the female pathway by activating a group of early female genes (i.e. cyp19a1, foxl2a, foxl2b, fst, bmp4, and fshb) and by repressing early testicular markers (i.e. dmrt1, nr0b1, sox9a1 and sox9a2). Feminization was induced in genetically allmale populations using 17a-ethynylestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 49 publications
9
45
0
2
Order By: Relevance
“…Taken together, we speculate that in the three-spot wrasse, DMRT1 was up-regulated in the presence of AI, presumably due to changes in the proportion of germ cell types in the testis. Our data are consistent with a report showing that DMRT1 transcript was not suppressed during the early process of estrogen-induced feminization in rainbow trout (Vizziano-Cantonnet et al 2008). Therefore, DMRT1 transcription might not be regulated by steroid hormones.…”
Section: Discussionsupporting
confidence: 93%
“…Taken together, we speculate that in the three-spot wrasse, DMRT1 was up-regulated in the presence of AI, presumably due to changes in the proportion of germ cell types in the testis. Our data are consistent with a report showing that DMRT1 transcript was not suppressed during the early process of estrogen-induced feminization in rainbow trout (Vizziano-Cantonnet et al 2008). Therefore, DMRT1 transcription might not be regulated by steroid hormones.…”
Section: Discussionsupporting
confidence: 93%
“…Such dimorphic expression pattern was also reported during gonadal sex differentiation and/ or hormone-induced sex reversal (Alam et al 2008, Ijiri et al 2008. By contrast, in rainbow trout oestrogen treatment up-regulates female specific genes but does not suppress all male specific genes during male-to-female gonadal trans-differentiation (Vizziano-Cantonnet et al 2008). These results together warrant a role for dmrt1 in testicular differentiation/spermatogenesis.…”
Section: Discussionsupporting
confidence: 65%
“…Probably, a negative feedback might have shut off the transcription of cyp19a1 to minimize the quantity of estrogens produced by the gonads because DES was already present. Earlier studies showed that treatment with E 2 and 17␣-ethynylestradiol to induce female sexual differentiation in European sea bass (5) and rainbow trout (30) resulted in reduced levels of cyp19a1 transcripts. Furthermore, studies using aromatase inhibitors for sex reversal in medaka (31,32) and other species (33) have also suggested a negative feedback relationship between estrogen levels and ovarian aromatase gene.…”
Section: Figmentioning
confidence: 99%